Sultan Ternate Iskandar Jabir Syah: Dari Konferensi Malino Hingga Menjadi Menteri Dalam Negeri Negara Indonesia Timur (NIT) 1946-1950 - Rustam Hasyim; Mustafa Mansur (ETNOHISTORI: Jurnal Ilmiah Kebudayaan dan Kesejarahan, 2015)
This study aims to reconstruct the political participation Iskandar Djabir Syah(Sultan of Ternate to 47) in the establishment of the State of East Indonesia. The focus ofthis study outlines some political events involving Iskandar Djabir Syah as the Malino andDenpasar conference to elected Minister of the Interior of Eastern Indonesia in the period1949-1950.The method used in this paper is a heuristic method that is history, criticism,interpretation and historiography. The results showed (1) Participation Sultan of TernateIskandar Djabir Syah the unitary state started early independence of the Republic ofIndonesia, is characterized by convening Malino and Denpasar conferences 1946.Formation of the State of East Indonesia became the inspiration for the political IskandarDjabir Syah to engage as a member of the Senate Negara Indonesia Timur/NIT representingNorth Maluku, as well as one of its disainer. (2) As one of the leaders who agreed to the ideaof van Mook to form a federalist country in Malino and Denpasar conference, so that whenthe formation of the State of East Indonesia was appointed Minister of the Interior in thecabinet of JE Tatengkeng period 1949-1950. (3) Malino to Denpasar Conference in 1946,initiated by HJ Dutch van Mook is an effort to establish the states in order to realize theUnited States of Indonesia (Republik Indonesia Serikat/RIS) based Linggarjati Agreement. Atthe conference formed the Eastern Indonesia State (Negara Indonesia Timur/NIT) covers anarea of Sulawesi, Sunda Kecil (Bali and Nusa Tenggara) and the Maluku Islands.